Environmental values and fire hazard of eucalypt plantings. Issue 11 (11th November 2016) - Jenkins, Meaghan; Collins, Luke; Price, Owen; Penman, Trent; Zylstra, Phil; Horsey, Bronwyn; Bradstock, Ross
Abstract: The revegetation of cleared landscapes with woody plants (termed "environmental planting") has the potential to sequester carbon (C), provide habitat, and increase biodiversity and connectivity. These environmental values are potentially offset by an increased fire hazard posed by revegetation. There is a need to understand the influence environmental planting has on landscape fire behavior and to determine how this changes as plantings age. This study examined how environmental values, regenerative capacity, fuel metrics, and potential fire behavior change with time since planting. We assessed 57 sites across the Albury‐Wodonga region (New South Wales, Australia). This included a range of environmental planting ages (4–40 yr time since planting), remnants, and pastures. Carbon storage increased with age of planting, with largest C stores found in remnants (105 tC/ha), while habitat complexity plateaued around 20 yr, with no significant difference between moderately aged plantings (14–20 yr), old plantings (>20 yr), and remnants. Modeled rate of fire spread was faster in pastures compared to environmental plantings and remnants. Flame height was slightly higher (0.5–1 m) in pastures than environmental plantings and remnants under a Very High Forest Fire Danger Index (FFDI), but this trend reversed under Extreme and Catastrophic conditions with flame heights greatest in environmental plantings and remnants albeit with slower rates of spread. This research highlights the importance of environmental plantings in the landscape in terms of C storage and environmental values and indicates the perceived hazard associated with rate of spread and flame height may not be justified at or less than Very High FFDI. However, at FFDI greater than Very High fire behavior may be significantly enhanced in environmental plantings and remnants. Further consideration needs to be given to the size and design of plantings and the type of species planted to fully develop an understanding of the complexities of fire risk. This study allows land managers to make informed decisions regarding the values and risks associated with revegetation of cleared landscapes with woody plants.